2018
DOI: 10.1155/2018/5830202
|View full text |Cite
|
Sign up to set email alerts
|

ATF4 Involvement in TLR4 and LOX-1-Induced Host Inflammatory Response to Aspergillus fumigatus Keratitis

Abstract: Purpose Activating transcription factor 4 (ATF4) is induced by various stressors. Here, we investigated the expression of ATF4 in the host inflammatory response to Aspergillus fumigatus (A. fumigatus) keratitis. Methods A. fumigatus keratitis mouse models developed by intrastromal injection as well as corneal epithelium scratching were examined daily with a slit lamp microscope for corneal opacification and ulceration. Subsequent in vitro experimentation was carried out in human corneal epithelial cells (HCECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, in macrophages and neutrophils, it was shown that HMGB1 upregulates LOX-1 through the DNA-binding domain BoxB [ 111 ]. Another inflammatory factor involved in the host immune response is activating transcription factor 4 (ATF4), which was shown to be dependent on LOX-1, ERK1/2, TLR4, and the JNK pathway in fungal keratitis [ 141 ]. It was also observed that inhibiting LOX-1 leads to a decrease in protein levels of adhesion factors such as VCAM-1, ICAM-1, P-selectin, E-selectin, and LFA-1.…”
Section: Pathogen-specific Interactionmentioning
confidence: 99%
“…Furthermore, in macrophages and neutrophils, it was shown that HMGB1 upregulates LOX-1 through the DNA-binding domain BoxB [ 111 ]. Another inflammatory factor involved in the host immune response is activating transcription factor 4 (ATF4), which was shown to be dependent on LOX-1, ERK1/2, TLR4, and the JNK pathway in fungal keratitis [ 141 ]. It was also observed that inhibiting LOX-1 leads to a decrease in protein levels of adhesion factors such as VCAM-1, ICAM-1, P-selectin, E-selectin, and LFA-1.…”
Section: Pathogen-specific Interactionmentioning
confidence: 99%
“…Then, a 33G Hamilton syringe is inserted into the tunnel to deliver a 1-2 µL inoculum directly into the underlying stroma. Regardless of fungal species, 10 5 total conidia is commonly used inoculum, although this can vary by a log-fold either way [1,32,[47][48][49][50][51][52].…”
Section: Intrastromal Injectionmentioning
confidence: 99%
“…For the inoculum, 5 µL of a conidial suspension (10 8 /mL for 2 groups using A. fumigatus ) or a non-specific smear of fungi can be applied to the debrided cornea, followed by contact lens placement. The contact lens must be secured in place by sewing the eyelids shut [ 31 , 51 , 53 , 54 , 55 ]. As an example of one such study, Huang et al performed an intrastromal injection of 10 8 /mL F. solani as described above and then placed a contact lens engineered to have antimicrobial properties onto the eye [ 56 ].…”
Section: In Vivo Modelsmentioning
confidence: 99%